The Cointegration approach in statistical arbitrage - Τριακόσιας, Ιωάννης (2023)
The goal of this work is to showcase the importance of the unit roots and how to appropriately manage them through the theory of cointegration. We present the practical connection of statistical arbitrage with the cointegration and how it can be applied in the Financial market. Also, we show why the cointegration is the cornerstone that connects the concepts of unit root, causality, statistical arbitrage and a valid statistical inference. After an extensive presentation of the theoretical background both from the Financial point of view as well as the statistical point of view of cointegration, we proceed with the application, where we manage to present the techniques used to achieve statistical arbitrage.